How work patterns affect leisure activities and energy consumption: A time-use analysis for Finland and France. (June 2021) - Klein, Franziska; Drews, Stefan; Savin, Ivan; van den Bergh, Jeroen
Highlights: Activity allocation associated with work time is more heterogeneous in France than in Finland. The relation between work duration and certain leisure activities is non-linear. Employment status can moderate the link between work time and energy use. Disaggregated time-use data can support design of energy, climate and labour-market policies. Abstract: Studies on socio-economic impacts of climate and energy policies tend to focus on income and expenditure effects. For analyses that go beyond monetary dimensions, time-diary data have proven to be useful. Here we investigate how work time relates to leisure activity structures and associated energy use for different types of employees. To this end, an analysis of time-use data is undertaken for Finland and France. Novel elements are (1) a differentiation between part-time and full-time employees, (2) the use of distinct energy intensities of different activities by household type instead of average energy intensities, and (3) allowing for non-linear relationships between work time and the allocation of other activities. Our results suggest that the effects of work time on energy use are rather homogeneous in Finland, whereas we find more differences between employee types in France. In both countries, adjustment of leisure-activity duration is sometimes strong initially but flattening for longer work hours. This relates to another finding, namely that the composition of leisure activities differs between people with distinct work hours. Our study suggests that analysis of disaggregated time-use data can add relevant insights for evaluation, and possibly design, of energy, climate and labour-market policies.